Estimating greenhouse gas emissions from port vessel operations at the Lagos and Tin Can ports of Nigeria - David O. Olukanni; Charles O. Esu (Cogent Engineering, 2018)
Greenhouse gas (GHG) emission, the number one contributor to global warming is not just a product of in-land transportation, industries and other anthropogenic effect but also the maritime and shipping industries. This article estimates the amount of greenhouse gases emitted from port vessel operations in the Lagos and Tin Can ports of Nigeria. The emission estimate was carried out based on the type of the vessel and its movement from the moment of its arrival (400 km from the coast). The emission estimate was done using the bottom-up approach based on the characteristics of individual vessels and using data on vessels processed by both ports in the first and second quarter of the year 2017. Among various types of vessels, Premium Motor Spirit (PMS) carriers are the heaviest emitters, followed by the container vessels and general cargo vessels. Result for the first and second quarter of 2017 indicates that approximately 16,335 t and 773 t of CO2 were produced and emitted during anchorage and while passing through lock gates movement, respectively. Also, 644 t of CO2 was emitted through maneuvering to the dock movement. Consequently, these three movements account for 85% of the total CO2 emission from Lagos and Tin Can ports. These emissions are known to contribute to lung cancer, cardio vascular and cardio pulmonary functions, allergies and asthma, particularly for the inhabitants of communities lying along the sea shore. However, if provisions are made for electricity from land, about 5% of the estimated emissions during cargo handling can be avoided.